Analysis Of The Quality Of Public Health Field - Siti Masitoh (Bandar Lampung University, 2015)
Community Health Center (Puskesmas) as providers of health care for the basic level in Indonesian society serves to maintain and improve public health. Through professionalism in the health centers provide health services, is expected to satisfaction of the public, especially the patients can continue to increase. The problem in this research is: What is the quality of health services provided Inpatient Health Center Kedaton Bandar Lampung. The aim of this study is to determine the quality of health care provided Inpatient Health Center Kedaton Bandar Lampung.Metode research used in this research is quantitative descriptive. Data collection method in this research is by way of literature study, observation, interviews, questionnaires and documentation. In this study using the technique of importance and performance analysis and determined the X ̿ (the average of the scores level performance) and Y ̿ (average of score of the level of interest) to further test the hypothesis that through t test or t test. The results showed that the overall satisfaction of patients Inpatient Health Center Kedaton Bandar Lampung well, but found a gap in the patient satisfaction factors justice delivery of health services for all patients. Furthermore, factors such facilities properly implemented, the responsibility of the officer, speed of service, and friendliness of the clerk. But to factors such as the provision of means of communication, the implementation of the basic rate for the patients, and timeliness of services, execution performance and interest rated mediocre or quite as well as to the certainty factor schedule of service and courtesy clerk, the patient considers these factors are excessive because it actually does not are expected by the patient.